The Modeling and Stress Analysis of Wind Turbine Blade - Hao Wang; Bing Ma; Jiaojiao Ding; Shuaibin Li (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
With the development of wind power generation technology, the wind turbine blade is becoming more and more important. Modeling and stress analysis of the wind turbine blade are very critical for the further design and the application of wind turbine blade. The small-scale wind turbine blade was focused on, considering the glass fiber reinforced plastic material. Based on the parameters of airfoil and the geometrical parameters of blade, the three-dimension model of blade was established with the modeling software. Then the model was introduced into ANSYS software to carry out the FEM analysis. According to the displacement solution of blade, the maximal displacement occurs in the blade tip while working, but it is less than the safety displacement of wind turbine. And the stress concentration occurs in the center of the blade, which corresponds to the comprehensive stress from the elastic stress solution of the wind turbine blade.Last, it can be found that the thermal stress does not play a major role from the thermal stress solution. The FEM results were compared with the tensile strength of the material and the safe displacement. Therefore, the effectiveness of FEM model and real safety of blade were verified. DOI : http://dx.doi.org/10.11591/telkomnika.v12i6.5536